Genomic characters of Anaplasma bovis and genetic diversity in China - Xiao-Yu Han; Li-Feng Du; Zhe-Tao Lin; Cheng Li; Tao Xiong; Wen-Jie Zhu; Run-Ze Ye; Ning Wang; Yi-Fei Wang; Wan-Ying Gao; Lin Zhao; Xiao-Ming Cui; et al. (Emerging Microbes and Infections, 2024)
ABSTRACTThe emergence of Anaplasma bovis or A. bovis-like infection in humans from China and the United States of America has raised concern about the public health importance of this pathogen. Although A. bovis has been detected in a wide range of ticks and mammals in the world, no genome of the pathogen is available up to now, which has prohibited us from better understanding the genetic basis for its pathogenicity. Here we describe an A. bovis genome from metagenomic sequencing of an infected goat in China. Anaplasma bovis had the smallest genome of the genus Anaplasma, and relatively lower GC content. Phylogenetic analysis of single-copy orthologue sequence showed that A. bovis was closely related to A. platys and A. phagocytophilum, but relatively far from intraerythrocytic Anaplasma species. Anaplasma bovis had 116 unique orthogroups and lacked 51 orthogroups in comparison to other Anaplasma species. The virulence factors of A. bovis were significantly less than those of A. phagocytophilum, suggesting less pathogenicity of A. bovis. When tested by specific PCR assays, A. bovis was detected in 23 of 29 goats, with an infection rate up to 79.3% (95% CI: 64.6% ∼94.1%). The phylogenetic analyses based on partial 16S rRNA, gltA and groEL genes indicated that A. bovis had high genetic diversity. The findings of this study lay a foundation for further understanding of the biological characteristics and genetic diversity of A. bovis, and will facilitate the formulation of prevention and control strategies.